Genome-Wide Identification of the Physic Nut WUSCHEL-Related Homeobox Gene Family and Functional Analysis of the Abiotic Stress Responsive Gene JcWOX5 - Tang, Yuehui; Li, Han; Guan, Yaxin; Li, Shen; Xun, Chunfei; Dong, Yanyang; Huo, Rui; Guo, Yuxi; Bao, Xinxin; Pei, Enqing; Shen, Qianmiao; Zhou, He; et al. (Frontiers in Genetics, 2020)
Plant-specific WOX transcription factors have important regulatory functions in plant development and response to abiotic stress. However, the identification and functional analysis of members of the WOX family have rarely been reported in physic nut until now. Our research identified 12 WOX genes (JcWOXs) in physic nut, and these genes were divided into three groups corresponding to the ancient clade, WUS clade, and intermediate clade. Expression analysis based on RNA-seq and qRT-PCR showed that most of the JcWOX genes were expressed in at least one of the tissues tested, whereas five genes were identified as being highly responsive to drought and salt stresses. Subcellular localization analysis in Arabidopsis protoplast cells showed that JcWOX5 encoded a nuclear localized protein. JcWOX5-overexpression plants increased sensitivity to drought stress, and transgenic plants suggested lower proline content and CAT activity, higher relative electrolyte leakage, higher MDA content, and higher rate of water loss under drought conditions. Expression of some stress-related genes was obviously lower in the transformed rice lines as compared to their expression in wild-type rice lines under drought stress. Further data on JcWOX5-overexpressing plants reduced drought tolerance verified the potential role of JcWOX genes in responsive to abiotic stress. Collectively, the study provides a foundation for further functional analysis of JcWOX genes and the improvement of physic nut crops.